Energy expenditure by multisensor armband in overweight and obese lactating women validated by doubly labeled water. (31st May 2013) - Slinde, F.; Bertz, F.; Winkvist, A.; Ellegård, L.; Olausson, H.; Brekke, H. K.
Abstract : Objective: To validate total energy expenditure (TEE) and activity energy expenditure (AEE) from the portable SenseWear armband (SWA) Pro 2 (TEESWA and AEESWA ; InnerView software versions SWA 5.1 and SWA 6.1) against TEE from doubly labeled water (DLW) and AEE from DLW and indirect calorimetry (TEEDLW and AEEDLW ) in overweight/obese lactating women at 10 weeks postpartum. Design and Methods: TEE was measured simultaneously with DLW (14 days) and SWA (first 7 days). Lactating women ( n = 62), non‐smoking, with a BMI > 25 kg/m 2 and wearing time SWA ≥ 90% were included. Results: Mean TEESWA5.1 was overestimated with 85 kcal/day compared to TEEDLW ( P = 0.040), while mean TEESWA6.1 was underestimated with 241 kcal/day compared to TEEDLW ( P < 0.001). Mean AEESWA5.1 was similar to mean AEEDLW ( P = 0.818), while mean AEESWA6.1 was underestimated with 581 kcal/day compared to AEEDLW ( P < 0.001). TEESWA6.1 and AEESWA6.1 were systematically underestimated at higher levels of energy expenditure and BMI while only AEESWA5.1 was systematically overestimated at higher levels of energy expenditure. Conclusions: TEESWA5.1 and AEESWA5.1 were fairly estimated on a group level while TEESWA6.1 and AEESWA6.1 were significantly and systematically underestimated. Both SWA software versions showed large individual variation in agreement with TEEDLW and AEEDLW, limiting the validity on individual level.